Natural enrichment of refined rapeseed oil with phenols and chlorophylls from olive leaves of Oblica cultivar - Majetić Germek, Valerija (Array, 2019)
Olive leaves as by-products of olive farming are rich natural source of bioactive compounds with antioxidant properties. In this study, the efficiency of the natural maceration of fresh and steam blanched olive leaves in refined rapeseed oil was investigated, as well as the effect of degree of leaf fragmentation (whole, cut, ground) and maceration time on transfer of bioactive compounds (polyphenols) and pigments (chlorophylls) in oil. In oils obtained by maceration, changes of total phenolic compounds and total chlorophylls were determined spectrophotometrically. The effect of these oil preparation procedures on oil quality indicators was also investigated through free fatty acid content and spectrophotometric indices. The content of total phenols and chlorophylls increased in oils obtained by maceration of fresh and steam blanched olive leaves, and were in statistically significant correlation with leaf fragmentation degree. The highest content of total phenols was achieved in oils with whole fresh leaves (220.4 mg/kg) after seven days of maceration while the chlorophylls transfer to oils was the most efficient when ground steam blanched leaves were macerated for 28 days (79.10 mg/kg). Maceration of olive leaves slightly deteriorated the quality of refined rapeseed oil, equally in oils with fresh and steam blanched olive leaves. This simple preparation procedure can be efficiently used for enrichment of refined oils with natural antioxidants.